Analysis of spectral efficiency of multiuser MISO downlink based on large-scale antennas - Ju-fang LI; Rui ZHAO; Bin JIANG; Yong-ming HUANG; Lv-xi YANG; Hai ZHANG (Tongxin xuebao)
The spectral efficiency of the downlink of multi-user multiple-input and single-output (MU-MISO) was ana-lyzed in the time-division duplex (TDD) communication systems with large-scale antennas. Assuming that the number of users was fixed and the antenna number (M) of base station (BS) increases without limit, the conclusions through theo-retical derivations and analyses were drawn that, when the transmit power of the BS reduces to 1/M of that of BS with single antenna, the system spectral efficiency tends to a constant value with the increase of M if the BS acquires the per-fect channel state information (CSI). The adverse effects of the inter-user interferences and the fast fading could also be eliminated through simple pre-processings. Although the multicell system is affected by the pilot contamination, which is the reason why the inter-cell interferences cannot be eliminated, the reduced transmit power makes the system changed from interference-limited to noise-limited. The limit expression of the system spectral efficiency using zero-forcing (ZF) normalized precoding is equal to that using maximum ratio transmission (MRT) normalized precoding. Finally, the lower bound of the spectral efficiency of multi-user downlink applying space time block code was presented and the correctness of the above conclusions was confirmed by the simulation analyses.